Analisis Perbandingan Tektonika Kayu Museum Wiswakarma dengan Museum Seni Modern Odunpazari - Ni Putu Sita Ananda Putri; Kadek Dwi Yoga Mahendra; Ida Bagus Gede Parama Putra; Gde Bagus Andhika Wicaksana (Program Studi Arsitektur, Fakultas Teknik Universitas Warmadewa, 2021)
Local cultural values ​​in architecture currently compete with modern culture in the midst of the current development of globalization. Tectonics in architecture is an effort to elevate the local cultural values ​​of an area. The understanding of tectonics includes solving the logical structure of a space, handling construction joints, processing skills and meeting materials so that they are able to bring out the expression of a building as an aesthetic value. Tectonics in architecture often uses wood materials. This wood material was chosen because wood is a renewable material and is not consumed by the times. Wood material is also still used as a building material from time to time. This study focuses on two buildings with the same function, namely the traditional Wiswakarma Museum building located in Gianyar and the Odunpazari Museum of Modern Art located in Turkey. The results of this study will show a comparison between the tectonics of traditional and modern wooden buildings.